Natural constituents from food sources: potential therapeutic agents against muscle wasting. Issue 11 (10th October 2019) - Shen, Shengnan; Yu, Hua; Gan, Lishe; Ye, Yang; Lin, Ligen
Abstract : Extracts and compounds from food sources could be developed as potential therapeutic agents for treating muscle wasting. Abstract : Skeletal muscle wasting is highly correlated with not only reduced quality of life but also higher morbidity and mortality. Although an increasing number of patients are suffering from various kinds of muscle atrophy and weakness, there is still no effective therapy available, and skeletal muscle is considered as an under-medicated organ. Food provided not only essential macronutrients but also functional substances involved in the modulation of the physiological systems of our body. Natural constituents from commonly consumed dietary plants, either extracts or compounds, have attracted more and more attention to be developed as agents for preventing and treating muscle wasting due to their safety and effectiveness, as well as structural diversity. This review provides an overview of the mechanistic aspects of muscle wasting, and summarizes the extracts and compounds from food sources as potential therapeutic agents against muscle wasting.